"Gone by lunchtime" : social policy, breakfast radio and the 2005 New Zealand election campaign : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Public Policy at Massey University - Belgrave, David (Massey University, 2006)
New Zealand's 2005 election was fought largely on ideological and social policy differences between the country's two largest political parties. The campaign was closely fought with opinion polls putting either the New Zealand Labour Party or the New Zealand National Party ahead at various times. Election campaigns are an important opportunity for policy debate as public interest in politics and the direction of policy is usually much higher than at other times. Parties attempt to convince voters that their policy programmes are sound and that their leaders are both capable and responsible. The media play an important role in allowing politicians to communicate their policies and personalities to the voter. In addition to direct political communication the media play an important role in debating politics and policy which becomes all the more important during an election campaign. Auckland has a saturated radio market with a large number of heterogeneous stations attempting to service niche demographics. Almost all of these have some news content. Using data collected from four Auckland breakfast radio shows this thesis attempts to explain the policy detail, ideology and personality-based appeals made by politicians on social policy in their attempt to sell their policy programme to the voter, while also exploring how this debate was covered by the breakfast radio shows. Both Labour and National Party politicians concentrated on policy detail and ideologically-based appeals when debating social policies. For both major parties those ideological appeals were, to some extent, contradictory to the targeting of their policies to middle-income voters. Meanwhile the analysis of this debate differed greatly from station to station, but on all stations examining social policies came second to reporting on the contest between to two parties to gain the Treasury Benches.
Keywords: Political campaigns; New Zealand; Parliament -- Elections, 2005